Modified proximal point algorithms involving convex combination technique for solving minimization problems with convergence analysis. (2nd August 2020) - Wairojjana, Nopparat; Pakkaranang, Nuttapol; Uddin, Izhar; Kumam, Poom; Awwal, Aliyu Muhammed
Abstract : In this paper, we are interested in solving minimization problem and common fixed point problem of finite family consisting asymptotically nonexpansive mappings in Hadamard spaces. For finding common solutions of their problems, we introduce a new modified proximal point algorithm involving convex combination technique. Under suitable conditions, Δ-convergence and strong convergence theorems are proved. Furthermore, we provide some numerical examples which show the efficiency and implementation of the proposed algorithm as well as show computational overview by comparing it with previously known algorithms.